1961
DOI: 10.1084/jem.113.2.451
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Two M Antigens in Certain Group a Streptococci Related to Type 14

Abstract: The type classification of Group A streptococci depends upon the M proteins, which are imrnunologically different for each type. These antigens are of special importance among the several well studied antigens of this group of streptococci because of their dose association with virulence. They are demonstrable by precipitin tests, and antibodies to them react type-specifically in active and passive animal protection tests and in ingestion and bactericidal tests. There have been described, up to the present tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1963
1963
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…There have been reports of a few strains of GAS which appear to express two M antigenic determinants according to immunological and biological studies. One study reported that most of the M14 strains examined also had the M51 antigen (Wiley and Wilson, 1960). Another study described a strain that possessed a second non-typable M protein in addition to Ml (El Kholy etai., 1975).…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of a few strains of GAS which appear to express two M antigenic determinants according to immunological and biological studies. One study reported that most of the M14 strains examined also had the M51 antigen (Wiley and Wilson, 1960). Another study described a strain that possessed a second non-typable M protein in addition to Ml (El Kholy etai., 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Antigens that stimulate cross-productive antibodies which act in only one direction have been reported in types 13 and 48 (6), types 14 and 51 (11), types 43 and 41 (12), and, in this paper, in types 46 and 51. The presence of bactericidal antibodies for type 46 and type 51 cocci in unabsorbed type 46 antiserum and the absence of reciprocal bactericidal antibodies in type 51 antiserum are analogous to the one-way cross reported by Wiley and Wilson for types 14 and 51 (11). Thus, although one can conclude that both types 14 and 46 cocci may contain type 51 M protein in addition to their homologous M protein, its presence in the two types appears to be dependent upon different factors.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, although one can conclude that both types 14 and 46 cocci may contain type 51 M protein in addition to their homologous M protein, its presence in the two types appears to be dependent upon different factors. In a study of 42 strains previously identified as type 14, Wiley and Wilson (11) found that 37 of the strains possessed both type 14 and type 51 M protein, 4 strains had only type 51 M protein, and 1 strain had only type 14 M protein. Representive strains of each type, that is, types 14, 14-51, and 51, were isolated from patients with streptococcal infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect Bactericidal Tests.--The details of this test are given in another publication from this laboratory (7). Briefly, it consists of rotating mixtures of dilutions of streptococci grown in filtered beef heart infusion broth (0.1 ml), normal rabbit serum or antiserum (0.05 ml), and heparinized normal human blood (0.25 ml) in silicone-stoppered, 7 X 10 mm glass test tubes for 3 hr at 37°C.…”
Section: Double Diffusionmentioning
confidence: 99%